100 jaar na Kuyper en Bavinck overwegingen bij de internationale belangstelling voor het neocalvinisme - Belt, Henk van den 1971- (2022)
This article offers a survey of recent scholarship partly occasioned by the commemoration of the death of Abraham Kuyper (1837-1920) and Herman Bavinck (1854-1921). Next to the digital disclosure of the archives and some biographical works, the attention for Kuyper's political and societal views and Bavinck's dogmatic and philosophical legacy among Anglophone theologians is striking. The lasting relevance of Dutch neoCalvinism appears to lie especially in its ability to deal with plurality in society and to apply the orthodox Reformed tradition to the contemporary (post)modern context.